Propuesta para el desarrollo sostenible de las zonas afectadas por el conflicto armado con las FARC-EP, potencializando el sector agrícola (2017)
Iillustrates the exploration that recurs to specify four departments of Colombia in which they were affected by the armed conflict with the Farc-Ep generating a negative effect in the agricultural sector, then determine the products that will be included according to the matrix Of interest based on the commercial policy of Colombia due to the analysis of products by their area harvested, their respective yield and the total of the production in the area under study. Finally, it establishes the instrumentalization of a road map to build agricultural zones competitive for the international market through fundamental axes for the development of the sector.